Minat Berwirausaha Lulusan Sma/Smk/Ma Ditinjau Dari Peluang Usaha Dan Lingkungan Keluarga Di Kelurahan Mlese Kecamatan Ceper Kabupaten Klaten - RAHMAWATI, ARIFAH; , Dr. Wafroturrohmah, S.E. MM (2015)
The purpose of this study was to determine: 1) Effect of business opportunities to the interest in entrepreneurship graduate SMA / SMK / MA in Sub Mlese Ceper District of Klaten district; 2) The influence of family environment on interest in entrepreneurship graduate SMA / SMK / MA in Sub Mlese Ceper District of Klaten district; 3) Effect of business opportunities and family environment on interest in entrepreneurship graduate SMA / SMK / MA in Sub Mlese Ceper District of Klaten district. This type of research, quantitative descriptive drawing conclusions through statistical analysis. The research sample according krejcie table with a 5% error level a number of 84 people from a population of 114 people. Collecting data using questionnaires. Data were analyzed using multiple linear regression analysis, t test, F test, test R2, as well as the effective contribution and relative contribution. Results of regression analysis to obtain the equation: Y = 16.127 + 0,326X1 + 0,336X2. 1) no influence on the interest in entrepreneurship business opportunities. This is evident from the results of the t test first obtain thitung> ttable ie 2.412> 1.990 and the significance value <0.05 is 0.018. 2) there is the influence of family environment on interest in entrepreneurship. This is evident from the results of the t test both gained thitung> ttable, namely 2.229> 1.990 and the significance value <0.05 is 0.029. 3) there is the influence of business opportunities and family environment on interest in entrepreneurship. This is evident from the test results gained Fhitung F> F table, namely 7.178> 3.11 and a significance value <0.05 is 0.001. 4) variable business opportunities provide effective contribution of 8% and the relative contribution of 53%, family environment variables contribute effectively amounted to 7.05% and the relative contribution of 47%. Results of calculation for the value of R2 obtained yield was 0.151, which means 15.1% interest in entrepreneurship and business opportunities are influenced by the family environment, the remaining 84.9% is influenced by other variables not examined in this study. Keywords: interest in entrepreneurship, business opportunities, and the family environment.